2019
DOI: 10.1039/c9an00306a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive SERS detection of specific oligonucleotides based on Au@AgAg bimetallic nanorods

Abstract: We synthesized a novel and sensitive Au/Ag bimetallic SERS-active nanotag, Au–Ag–Ag core–shell–shell nanorod (Au@AgAgNR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Among all noble metals, Ag nanocrystals have the best SERS activity, but Au nanocrystals are more stable than Ag nanocrystals. Combining Au and Ag can make full use of their individual advantages and synergistic effects for improved chemical and plasmonic properties 24 . Most recently, researchers found that sandwich structures prepared by embedding semiconductors in two layers of plasmonic noble metals showed very high Raman enhancement due to multidimensional plasma coupling 25 .…”
mentioning
confidence: 99%
“…Among all noble metals, Ag nanocrystals have the best SERS activity, but Au nanocrystals are more stable than Ag nanocrystals. Combining Au and Ag can make full use of their individual advantages and synergistic effects for improved chemical and plasmonic properties 24 . Most recently, researchers found that sandwich structures prepared by embedding semiconductors in two layers of plasmonic noble metals showed very high Raman enhancement due to multidimensional plasma coupling 25 .…”
mentioning
confidence: 99%
“…The sample solution containing the analyte can be an extract from a real sample (i. e., mostly for food and agricultural applications) or a body-fluid from human or animal (i. e., for biomedical applications). Ning et al [158] functionalized the Au@Ag core-shell nanorods with a Raman reporter molecule and specific DNA (i. e., DNA1) to detect the HPV-16 gene. In parallel, a magnetic bead has also been functionalized with another DNA (i. e., DNA2), where the two designed DNAs were complementary to the target gene of HPV-16.…”
Section: Sers Detection Of Analyte In Solutionmentioning
confidence: 99%
“…On the other hand, metal NPs functionalized with different recognition elements allows the simultaneous detection of multiple analytes, which approach is also known as the Figure 11. a) Schematic illustration of colloidal biosensor using DNA-functionalized Au@AgAg nanorod as SERS probe (top) for the detection of gene HPV-16 using magnetic bead (bottom), [158] b) Synthesis of anisotropic Au nanorod/Polyaniline nanoparticles by a microfluidics approach (top) and change in the Raman intensity in the presence of different ions (bottom), [163] c) development of polymer-coated Au nanorod for simultaneous detection of different Raman active analytes (MO, FITC and R6G) via electrostatic interaction or hydrogen binding, [182] d) Simultaneous detection of ochratoxin A and aflatoxin B1 by selfassembly of Au nanoparticles around magnetic nanoparticle via the hybridization of designed aptamers and their complementary DNAs. [192] plasmonic nose.…”
Section: Sers Detection Of Analyte In Solutionmentioning
confidence: 99%
“…Ning et al also demonstrated SERS performances obtained by using Au–Ag–Ag nanorod coupled to the magnetic beads through DNA hybridization. A LOD of 1 fM for HPV-16 fragments (human papillomavirus DNA type 16) was found [ 77 ]. Hussain et al reported on the quick contaminant detection in milk by using Au/Ag core-shell nanoparticles.…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%